Analysis of Waste Management and Greenhouse Gas Emission Reduction (Case Study: Adiwiyata School SMPN 18 Surabaya and Non-Adiwiyata School SMPN 31 Surabaya) - Bhakti, Wahyu Satria; Ni'am, Achmad Chusnun; Nurbia, Nurbia; Prasetyaningtyas, Dyan (Journal of Earth and Marine Technology (JEMT), 2024)
In Surabaya, a city program named "Perilaku dan Berbudaya Lingkungan Hidup di Sekolah" (PBLHS), or Environmental Behavior and Culture in Schools, specifically targets Adiwiyata schools to promote sustainable practices. However, not all schools participate in this initiative. Non-Adiwiyata schools typically send their waste to the Final Waste Processing Site (TPA), which exacerbates the load on these facilities and contributes to increased greenhouse gas (GHG) emissions. This study aims to compare waste management and GHG reduction efforts between Adiwiyata and non-Adiwiyata schools in Surabaya. We conducted sampling at one Adiwiyata school and one non-Adiwiyata school, analyzing waste generation and management strategies using the SNI 19-3964-1994 method. Our findings reveal that Adiwiyata schools generate less waste, with an average of 0.0103 kg/person/day, compared to 0.0155 kg/person/day at non-Adiwiyata schools. Furthermore, the organic waste composition was significantly lower in Adiwiyata schools at 2.08%, versus 33% in non-Adiwiyata schools. Methane (CH4) emissions from Adiwiyata schools were also lower, measuring 0.123 Gg/year, as opposed to 0.405 Gg/year from non-Adiwiyata schools. These disparities in waste output, organic waste composition, and GHG emissions are significantly influenced by the environmental knowledge, attitudes, and practices within the school communities.